Persepsi Wisatawan Nusantara Terhadap Makanan Tradisional Dalam Perkembangan Wisata Kuliner di Kota Blitar, Jawa Timur - Kristiana, Nina Indra; Putra, I Nyoman Darma; Kumbara, A.A. Ngurah Anom (Journal of Hotel Management, 2023)
This research aimed to investigate the importance of traditional culinary in supporting the growth of culinary tourism in Blitar City, East Java. The study focused on the perception of local tourists toward traditional food and the role of the government and traditional food in tourism development. Data was collected using interviews, questionnaires, observations, and documentation. The data analysis was conducted using both descriptive qualitative and statistic descriptive methods. The findings revealed that the perception of local tourists toward traditional food and beverages in Blitar City was "very good", with the service, cleanliness, food's price, and atmosphere categorized as good. The government of Blitar City played a vital role in supporting the development of traditional culinary, including supervising, evaluating, promoting, holding cooperation with stakeholders, developing infrastructure, training local tourism guides, and holding tourism workshops and seminars. This research suggests that traditional culinary is a crucial aspect in the growth of culinary tourism in Blitar City, and the government's support is crucial to promote and develop it further.